Biblical Hermeneutics of Food in Times of Pandemic - Erbele-Küster, Dorothea 1969- (2023)
Biblische Texte reagieren auf Krisensituationen mit verschiedenen literarischen und rhetorischen Strategien, wobei Nahrung eine zentrale Rolle spielt. Der Artikel skizziert die Merkmale der Abhängigkeit von Nahrung in diesen unterschiedlichen Formen der Krisenliteratur. Er bietet einen Überblick über die wichtigsten Merkmale einer Hermeneutik der Nahrung in biblischen Texten vor dem Hintergrund der Covid-19 Pandemie.
Biblical texts have responded to situation of crisis with different literary and rhetorical strategies often referring to food, its production and consumption. The article sketches the characteristics of human dependency on food in the different forms of crisis literature. It offers an overview on key features of hermeneutics of food in biblical texts on the backdrop of the Covid-19 pandemic.